2020
DOI: 10.1002/advs.201902900
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced Structural Evolution and Bandgap Optimization of Lead‐Free Halide Double Perovskite (NH4)2SeBr6

Abstract: Lead‐free halide double perovskites (HDPs) are promising candidates for high‐performance solar cells because of their environmentally‐friendly property and chemical stability in air. The power conversion efficiency of HDPs‐based solar cells needs to be further improved before their commercialization in the market. It requires a thoughtful understanding of the correlation between their specific structure and property. Here, the structural and optical properties of an important HDP‐based (NH4)2SeBr6 are investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…[13][14][15] L. Wang et al reported on the inuence of lead halide perovskite CH(NH 2 ) 2 PbBr 3 and found that the structural phase is changed at 2.2 GPa. 16 Pressuredependent samples undergo band-gap energy shrinkage and the electron orbits move toward the electric eld. As a result, the bonding energy is changed within the octahedral state, which mostly affects the boundary conditions of the electronic wave functions and brings about a reduced band gap energy.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] L. Wang et al reported on the inuence of lead halide perovskite CH(NH 2 ) 2 PbBr 3 and found that the structural phase is changed at 2.2 GPa. 16 Pressuredependent samples undergo band-gap energy shrinkage and the electron orbits move toward the electric eld. As a result, the bonding energy is changed within the octahedral state, which mostly affects the boundary conditions of the electronic wave functions and brings about a reduced band gap energy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al. [ 100 ] and Liang et al. [ 82 ] conducted DFT calculations and observed a distinct tendency of the bond length shortening in the (NH 4 ) 2 SeBr 6 and CsPbI 3 structures in response to pressure.…”
Section: Mhps Anisotropic Characteristicsmentioning
confidence: 93%
“…All experimental data are extracted from refs. [ 34–37,40–42,49,51,52,55,57,58,60,61,63–66,68,70,72,74,80,82,84,87–92,96–100 ] .…”
Section: Mhps Subjected To Stress/strainmentioning
confidence: 99%
“…[115] Selenium has also been considered as an alternative to lead, in particular in the vacancy ordered ðNH 4 Þ 2 SeBr 6 perovskite. [116] At room conditions the compound is cubic with space group Fm3m, and transforms to a tetragonal P42 phase above 11 GPa as a result of the rotation of the ½SeBr 6 2À octahedra. [116] The cubic and the tetragonal phases have bulk moduli of 22.28 and 131.91 GPa, respectively, suggesting that the tetragonal phase has a more robust structure that could contribute to the stability of the solar cell.…”
Section: Other Structuresmentioning
confidence: 99%
“…[116] The cubic and the tetragonal phases have bulk moduli of 22.28 and 131.91 GPa, respectively, suggesting that the tetragonal phase has a more robust structure that could contribute to the stability of the solar cell. [116] 3. From Fundamental Studies to Applications Despite the promising and interesting results obtained in situ, there is still a gap between fundamental studies and actual applications in operating devices.…”
Section: Other Structuresmentioning
confidence: 99%